Eliminação de parâmetros perturbadores na estimação de tamanhos populacionais - Festucci, Ana Claudia (2010)
In this study, we used the capture-recapture procedure to estimate the size of a closed population. We analysed three di_erent statistics models. For each one of these models we determined - through several methods of eliminating nuisance parameters - the likelihood function and the pro_le, conditional, uniform integrated, Je_reys integrated and generalized integrated likelihood functions of the population size, except for the last model where we determined a function that is analogous to the conditional likelihood function, called integrated restricted likelihood function. In each instance we determined the respectives maximum likelihood estimates, the empirical con_dence intervals and the empirical mean squared errors of the estimates for the population size and we studied, using simulated data, the performances of the models.